2021
DOI: 10.1021/acs.jpcc.1c00550
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging and Location of Pb2+ and K+ in EMT Framework-Type Zeolite

Abstract: The understanding of the structural framework and metal locations within zeolites are two critical aspects to tune and further exploit their properties as heterogeneous catalysts, advanced optical devices, or as water remediation materials. The development of electron microscopy has made it possible to observe directly the zeolitic framework and the distribution of extra framework cations within the pores at the atomic level. Here, we have studied the EMT framework providing data with an unprecedented spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The visibility of the oxygen atom was already attained in the raw OBF image before unit-cell averaging. The SNR of the S/TEM images of zeolites is usually enhanced by averaging the raw data using a priori knowledge about the sample, such as the space groups of the material ( 27 , 28 ). Although this is effective for homogeneous bulk structure analyses, it cannot be applied to heterogeneous or nonperiodic local structure analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The visibility of the oxygen atom was already attained in the raw OBF image before unit-cell averaging. The SNR of the S/TEM images of zeolites is usually enhanced by averaging the raw data using a priori knowledge about the sample, such as the space groups of the material ( 27 , 28 ). Although this is effective for homogeneous bulk structure analyses, it cannot be applied to heterogeneous or nonperiodic local structure analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, C s -corrected STEM was also used to study the local information of K + and Pb 2+ cations in the K-exchanged and Pb-exchanged EMT -type zeolites, respectively. Based on the C s -corrected STEM images, it can be concluded that both Pb 2+ and K + cations are nonperiodically distributed in the pores, and the Pb 2+ is preferentially located in the t-wof cage and K + is located in the t-wou cage . Such atomic-resolution visualization indicates a substantial increase in the information limit in terms of sensitivity and spatial resolution.…”
Section: Characterization Methodsmentioning
confidence: 93%
“…Based on the C s -corrected STEM images, it can be concluded that both Pb 2+ and K + cations are nonperiodically distributed in the pores, and the Pb 2+ is preferentially located in the t-wof cage and K + is located in the t-wou cage. 343 Such atomicresolution visualization indicates a substantial increase in the information limit in terms of sensitivity and spatial resolution. Note that direct observation of transition-metal single atoms with much smaller Z-number in zeolite frameworks remains a big challenge.…”
Section: Spherical Aberration-corrected Scanning Transmission Electro...mentioning
confidence: 99%
“…Atomic-level imaging of zeolites using electron microscopy, especially imaging of the active sites, is essential to deeply understanding their chemical behavior and becomes indispensable in order to rationally design materials with targeted properties. Zeolites, as one of the most important kinds of porous materials, have been widely used in catalysis, selective separation, and so on, due to their particular structures. High-resolution imaging of zeolites has been very challenging, as they are extremely sensitive to electron beams. Therefore, exploration of new electron microscopy imaging techniques and methodology that would enable the direct imaging of zeolites at the atomic level is highly desirable. The implementation of aberration correctors and low-dose imaging techniques has allowed the direct visualization of zeolite framework T (T = Si, Al, Ge, etc.)…”
mentioning
confidence: 99%